PENERAPAN METODE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) BERBASIS AUDIOVISUAL DALAM PEMBELAJARAN DARING MENULIS TEKS ANEKDOT PADA SISWA KELAS X SMK KESFAM - Nurillah Shalihatul Mubarokah; Wikanengsih Wikanengsih; Tamtam Kamaludin (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
On the pandemic now this, learning is required and where required done at home in order to break the spread of Covid-19, i.e with distance learning (online). in online learning also teachers and stundents are required to more creative as possible. This research is done to examine learning and Students Team Achievement Division (STAD) – based Audiovisual on VOCATIONAL students of class X SMK KESFAM. Motivated by the many obstacles in the learning process in the network (online) to students who have difficulty pouring ideas and idea in form of writing which is caused by the lack of understanding of the students to the structure, the steps of writing, text, and the rules of language that right in writing the text of anecdote. This study aims to enhance creativity in writing the text anecdote - based audiovisual and find aout the students ‘response to the implementantion of the learning in the network (online) by the method of student Team Achievement Division (STAD). Methods this research is a descriptive qualitative. Data colletion techniques carried out by way of test, observation, and questionaries. The results of the study show that learning in the network (online) write a text anecdote on the students of class X SMK KESFAM. Through the method of cooperative learning and Student Team Achievement Division (STAD) – based Audiovisual running optimally it can be seen from the results expressed by students through the learning outcomes increased to exceed the average value of KKM namely 85.5 by looking at the average value in the structure is at 80.5 and the value of the rules of language is 75.5 anget done and learning with the use of audiovisual media also has the effectiveness to support the writing skills of students in the text of the anecdote.